2006
DOI: 10.1186/1471-2474-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Problems and needs for improving primary care of osteoarthritis patients: the views of patients, general practitioners and practice nurses

Abstract: Background: Osteoarthritis (OA) is highly prevalent and has substantial impact on quality of life as well as on healthcare costs. The general practitioner (GP) often is the first care provider for patients with this chronic disease. The aim of this study was to identify health care needs of patients with OA and to reveal possible obstacles for improvements in primary care management of OA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
139
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(143 citation statements)
references
References 26 publications
1
139
1
2
Order By: Relevance
“…This observation is important, as it indicates that there may be specific treatment priorities that need to be targeted before other aspects of patient care (e.g., ability to cope) can be improved and a PEP can be contemplated [19] Such priorities in treatment, according to our data, are pain control and alleviation of depression. This means that treatment protocols may need to be tailor made for each patient or patient group.…”
Section: Resultsmentioning
confidence: 62%
“…This observation is important, as it indicates that there may be specific treatment priorities that need to be targeted before other aspects of patient care (e.g., ability to cope) can be improved and a PEP can be contemplated [19] Such priorities in treatment, according to our data, are pain control and alleviation of depression. This means that treatment protocols may need to be tailor made for each patient or patient group.…”
Section: Resultsmentioning
confidence: 62%
“…There is also a risk that patients with OA can enter a cycle whereby depression can lead to fatigue, which in turn can lead to the avoidance of activity (Rosemann et al, 2007a) and thus muscle de-conditioning, increased pain and increased social isolation. This cycle can mean that general practitioners (GPs) find it difficult to distinguish between complaints related to the disease and those symptoms related to concomitant depression (Rosemann et al, 2006). Memel, Kirwan, Sharp, and Hehir (2000) have found that GPs often lack enough knowledge about anxiety and depression in patients with OA and hence miss their diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it difficult for physicians to distinguish between patients with poor and good prognoses at an early stage of the disease. As a result, many patients with early OA are not sufficiently informed about their likely course of activity limitations, and are not referred for appropriate treatment (9,10). This is unfortunate, because developing activity limitations is one of the main fears of patients with OA (9).…”
Section: Introductionmentioning
confidence: 99%